Early Pleistocene hominin teeth from Gongwangling of Lantian, Central China. Issue 168 (July 2022) - Pan, Lei; Zanolli, Clément; Martinón-Torres, María; Bermúdez de Castro, José María; Martín-Francés, Laura; Xing, Song; Liu, Wu
Abstract: The fossil hominin individual from Gongwangling of Lantian, Central China, represents one of the earliest members attributed to Homo erectus in East Asia. Recent paleomagnetic analyses have yielded an age of 1.63 Ma for the Gongwangling hominin. The fossils from this site are critical to characterize the morphological features of early hominins in East Asia and to understand their relationships with other earlier and later members of the genus Homo . However, most morphological details of the Gongwangling cranium were obliterated due to postmortem erosion and deformation. Here we used high-resolution microcomputed tomography and three-dimensional virtual imaging techniques to extract the teeth and reconstruct the worn/damaged areas, describe the external morphology, measure crown diameters, record nonmetric traits of the crown and root, and investigate the shape of the enamel-dentine junction using geometric morphometrics. We compared the data obtained from the six teeth of the Gongwangling hominin with African early Homo, African and Georgian Homo erectus s.l., Asian Homo erectus, Homo antecessor, pre-Neanderthals, Neanderthals, and modern humans. Our results show that the Gongwangling specimens display affinities with other specimens attributed to H. erectus s.l. The highly divergent and noncoalesced three-root system in the Gongwangling specimens is comparable to that in the Early Pleistocene members of H. erectus s.l., and differs from Middle Pleistocene representatives of the species. The enamel-dentine junction shape of the Gongwangling molars prefigures the Asian H. erectus pattern later found in East Asian Middle Pleistocene H. erectus . The morphological comparisons between East Asian Early Pleistocene (e.g., Gongwangling, Meipu, and Quyuan River Mouth) and Middle Pleistocene H. erectus (e.g., Zhoukoudian, Hexian, and Yiyuan) suggest a potential temporal trend within this species in East Asia.